2007
DOI: 10.1007/s11157-006-9114-z
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of methane generated from landfills by biofiltration: a review

Abstract: The production of biogas in landfills, its composition and the problems resulting from its generation are all reviewed. Biofiltration is a promising option for the control of emissions to atmosphere of the methane contained in biogas issued from the smaller and/or older landfills. A detailed review of the methane biofiltration literature is presented. The microorganisms, mainly the methanotrophs, involved in the methane biodegradation process, and their needs in terms of oxygen and carbon dioxide utilization, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
2
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(99 citation statements)
references
References 141 publications
1
86
2
7
Order By: Relevance
“…The maximum elimination capacity (EC max ) recorded over the course of testing was 66 g/m 3 /h for an inlet load (IL) of about 95 g/m 3 /h. These results are comparable to the best purification performance identified by Nikiema et al [19]. Over the first 30 days of operation (month of September), the concentration of CH 4 at the biofilter's inlet was maintained at < 2% v/v (i.e., 20,000 ppmv) by adjusting the flow rate of the diluting ambient air.…”
Section: Analytical Monitoringsupporting
confidence: 85%
“…The maximum elimination capacity (EC max ) recorded over the course of testing was 66 g/m 3 /h for an inlet load (IL) of about 95 g/m 3 /h. These results are comparable to the best purification performance identified by Nikiema et al [19]. Over the first 30 days of operation (month of September), the concentration of CH 4 at the biofilter's inlet was maintained at < 2% v/v (i.e., 20,000 ppmv) by adjusting the flow rate of the diluting ambient air.…”
Section: Analytical Monitoringsupporting
confidence: 85%
“…Flaring, incineration and energy recovery could be considered, but only if the waste gases are concentrated, for example, by membrane separation processes (Bandara et al, 2011), dissipation chamber (this article) or by mixing gas streams rich in CH 4 (eg: biogas). However, these treatment techniques can only be economically viable when the amount of gas stream to be treated exceeds 10-15 m 3 h -1 , and if the stream CH 4 concentration remains greater than 20% v/v (Nikiema et al, 2007). If data obtained in this study (including biogas production -data not shown) are used, the mixture of biogas with the residual gas flow obtained with the dissipation technique would result in a dilution of 10 to 20-fold.…”
Section: Management Of the Waste Gasesmentioning
confidence: 94%
“…Thus, while the content of hydrogen sulfide would have an important reduction, to around 500 ppm, the methane content would drop to values as low as 6% in the mixture of biogas and waste gas, posing serious difficulties and technical problems, including risks of an explosive atmosphere within the range of 5 to 15% CH 4 (Noyola et al 2006). On the other hand, in research related to landfills, coal mining and piggery, there are many studies on biofiltration of CH 4 at low concentrations (250-50,000 ppm v ), since in these fields problems related to greenhouse gas emissions are well known (Sly et al, 1993;Melse and Vander Werf, 2005;Gebert and Gröngröft, 2006;Nikiema et al, 2007;Park et al, 2009). However, we did not find in the literature any study regarding the removal of CH 4 from waste gases generated in anaerobic reactors used for the treatment of domestic wastewater, possibly because of the different requirements for the biofiltration of CH 4 in relation to odorant compound biofiltration and because of CH 4 mass-transfer limitatios in biofilms, which often reduce the abatement potential or lead to an empty bed residence time (EBRT) extremely high.…”
Section: Management Of the Waste Gasesmentioning
confidence: 99%
“…Recent reviews and experimental work on biological treatment of methane technology have shown that with optimization of liquid nutrient feeds, loading rates, and biofilter configuration, retention times can be significantly reduced and loading rates increased without compromising removal efficiency (Nikiema et al, 2009a;2007). Mass transfer limitations traditionally associated with biological conversion of CH 4 have been alleviated by adding an additional liquid phase (silicone oil), which helps improve the solubility of methane into the liquid phase (Rocha-Rios et al, 2009).…”
Section: Tà20mentioning
confidence: 99%
“…These can be subject to high capital costs, generate secondary pollutants, and have high maintenance costs (Phillips, 2008). Therefore, gas treatment using biological methods is being employed more frequently due to the inherent advantages, including (i) neutralization of the pollutant, (ii) low capital and maintenance costs, and (iii) good overall performance (Nikiema et al, 2007). The treatment of CH 4 emissions in biofilm reactors has become an established technique in recent years.…”
Section: Introductionmentioning
confidence: 99%